Experimental and Theoretical Study of Parabolic Trough Solar Collector Performance Without Automatic Tracking System - Khudir Zarrag; Fayadh M. Abed; Salim. Y. Kasim (مجلة جامعة الانبار للعلوم الصرفة, 2021)
In this research, a practical and theoretical study was conducted to evaluate the performance of parabolic trough collectors (PTCS) of length (3 m) and width (2.67 m) for three solar collectors connected in parallel, and the absorber tube is made of stainless steel with an internal and external diameter (0.028 m), (0.031 m), respectively. The absorber tube of length 11 m, was painted with un shiny black paint to increase the absorption of sunlight and reduces the thermal radiation. The working fluid is transferred through the receiver tube and located at the focus area of the three collectors. The collector width aperture width was 0.8 meters, and 2.40 meters length with rim angle of Ø = 90°, and concentration ratio of 8.02. The collector surface was covered with aluminum foil which is available in the local market (3M SA-85), which covers galvanized iron sheets with a thickness of 2 mm. A computer program in Fortran language was built to calculate the performance of the solar collector. Experimental results of the test showed that the performance factor of the solar collector is less than the typical type, where notes that there is a large deviation between the theoretical and experimental results, especially in the winter, where the deviation in the morning at ten o'clock about 78%, while it was 5% at noon. The large deviation value mentioned resulting from the assumptions that have been developed to simplify the equations that were used in the theoretical side of research, also the reasons that the theoretical results are taken on the assumption that weather conditions are clear sky and that contrary to reality in the winter. ةThe best efficiency of the solar collector was between solar time (12:00) and time (1:00) at night for two seasons, and the obtained results showed that the increase of mass flow rate of fluid from the amount of (0.033) kg/sec to the amount of (0.066) kg/sec increases the efficiency of solar collector, but leads to reduce the temperature difference between the inlet and exit, as well as the results showed that an increase in solar flux increases the useful energy obtained from the solar collector.